Indirect genetic effects and the lek paradox: inter-genotypic competition may strengthen genotype x environment interactions and conserve genetic variance - Danielson-François, Anne M; Zhou, Yihong; Greenfield, Michael D (Genetica, 2009)
Understanding the evolutionary mechanisms that maintain genetic variation in natural populations is one of the fundamental goals of evolutionary biology. There is growing evidence that genotype-by-environment interaction (G x E) can maintain additive genetic variance (V A), but we lack information on the relative performance of genotypes under the competitive situations encountered in the field. Competing genotypes may influence each other, and this interaction is also subject to selection through indirect genetic effects (IGE). Here, we explore how genotypes perform when interacting and evaluate IGE in order to understand its influence on V A for sexually-selected traits in the lesser waxmoth, Achroia grisella. We found that inter-genotype differences and crossover interactions under joint rearing are equal to or greater than values when reared separately. A focal genotype exhibited different performances when jointly reared with various genotypes--suggesting that IGE may be responsible for the increased levels of crossover and differences in performance observed. We suggest that some genotypes are superior competitors for food acquisition in the larval stage, and that these differences influence the development and evolution of other genotypes through IGE. We reaffirm the role of G x E in maintaining V A and note the general importance of IGE in studies of evolutionary mechanisms.